2010
DOI: 10.1590/s0100-84042010000100016
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia comparada da folha e espata de espécies de Anthurium (Araceae) ocorrentes na Mata Atlântica

Abstract: -(Comparative anatomy of leaf and spathe of Anthurium (Araceae) species from the Atlantic Rain Forest). Leaf and spathe anatomy of nine species of the genus Anthurium (sections Urospadix and Leptanthurium) were analyzed. Plant material was collected from different locations in Brazil and cultivated under identical conditions in the Instituto de Pesquisas Jardim Botânico do Rio de Janeiro. Our objective was to evaluate the diagnostic potential of leaf and spathe anatomy for taxonomic purposes. Leaves presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
4
8
0
Order By: Relevance
“…All Anthurium genotypes s studied in this work showed leaf epidermal cells with straight or wavy walls, corroborating the results obtained by Keating (2002) and Mantovani et al (2010). The epidermal cells in the leaves are short and have a random distribution.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…All Anthurium genotypes s studied in this work showed leaf epidermal cells with straight or wavy walls, corroborating the results obtained by Keating (2002) and Mantovani et al (2010). The epidermal cells in the leaves are short and have a random distribution.…”
Section: Resultssupporting
confidence: 91%
“…Similar results were reported by Mantovani et al (2010), who observed that the unornamented cuticle is a frequent feature in the Araceae family.…”
Section: Gmg Dias Et Alsupporting
confidence: 90%
See 3 more Smart Citations